2011
DOI: 10.1063/1.3658617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al/CuO reactive multilayer films additives on exploding foil initiator

Abstract: An investigation on the influence of Al/CuO reactive multilayer films (RMFs) additives on exploding foil initiator was performed in this paper. Cu film and Cu/Al/CuO RMFs were produced by using standard microsystem technology and RF magnetron sputtering technology, respectively. Scanning electron microscopy characterization revealed the distinct layer structure of the as-deposited Al/CuO RMFs. Differential scanning calorimetry was employed to ascertain the amount of heat released in the thermite reaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 13 publications
0
57
0
Order By: Relevance
“…Nanostructured semiconductor films composed of thin layers of nanostructured objects such as nanoparticles, nanorods, nanowires or nanoporous networks with variable grain size and controlled porosity can exhibit properties superior to conventional thin films due to the deliberate engineering of nanoscale features into their structure and these films have practical applications in areas such as photovoltaics, electrochemical sensors, photoelectrochemical water splitting, biosensors and as antireflection layers. [1][2][3][4][5] Techniques such as thermal evaporation, 6 pulsed laser deposition, 7 DC and RF sputtering, 8,9 plasma evaporatihon, 10 sol-gel technique, 11 molecular beam epitaxy, 12 electrodeposition 13 and chemical vapor deposition 14 have been employed for the synthesis of nanostructured thin films of different semiconductors. Another technologically logical strategy for creating nanostructured films is the alignment of nanoparticle building blocks into ordered superstructures with non-resistive inter-particle contacts by bottom-up approaches and is one of the recent key topics in the area of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured semiconductor films composed of thin layers of nanostructured objects such as nanoparticles, nanorods, nanowires or nanoporous networks with variable grain size and controlled porosity can exhibit properties superior to conventional thin films due to the deliberate engineering of nanoscale features into their structure and these films have practical applications in areas such as photovoltaics, electrochemical sensors, photoelectrochemical water splitting, biosensors and as antireflection layers. [1][2][3][4][5] Techniques such as thermal evaporation, 6 pulsed laser deposition, 7 DC and RF sputtering, 8,9 plasma evaporatihon, 10 sol-gel technique, 11 molecular beam epitaxy, 12 electrodeposition 13 and chemical vapor deposition 14 have been employed for the synthesis of nanostructured thin films of different semiconductors. Another technologically logical strategy for creating nanostructured films is the alignment of nanoparticle building blocks into ordered superstructures with non-resistive inter-particle contacts by bottom-up approaches and is one of the recent key topics in the area of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…More recently,t hermite materials were also considered to produce gas species or pressure bursts, opening new potential fields of application such as pressure mediated molecular delivery [23,24],b iological agent inactivation [25][26][27],h ydrogen production [28,29],o rp ropulsion systems [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…19a Ni melt, experimentally measured by means of quasielastic neutron 1396 scattering at 1928 K, was found to be equal to 4.9 Â 10 À9 m 2 /s 1397 [138]. Therefore, if we assume that the reaction is controlled by dif- ing foil initiator was studied in the work [146]. It was concluded 1507 that the reactive multilayer foil has the potential to decrease the 1508 initiation threshold, which will lead to a smaller volume of initia-1509 tor, further increasing safety and reliability.…”
mentioning
confidence: 95%
“…This 140 review places emphasis on material science aspects of nano-struc- 141 tured reactive systems. 142 Analysis of recent research papers on heterogeneous combus- 143 tion has clearly revealed that the new classes of reactive systems, 144 which are characterized by nanosized-scale and possess extremely 145 high reactivity, as compared to similar reactive systems with 146 micro-scale heterogeneity, has attracted the attention of 147 researchers and has dominated R&D. The present paper gives an 148 overview of four classes of such reactive nano-media: (i) mechani- 149 cally-structured composites; (ii) sol-gels; (iii) mixtures of metal 150 and metal-oxide nanopowders, i.e., so-called, super thermite 151 compositions and (iv) multilayer nano-foils. Research in each of 152 these areas is being performed almost independently and cross- 153 references are rare.…”
mentioning
confidence: 99%